Somatosensory evoked magnetic fields caused by mechanical stimulation of the periodontal ligaments. Issue 5 (May 2022) - Shimada, Eriya; Kanetaka, Hiroyasu; Hihara, Hiroki; Kanno, Akitake; Kawashima, Ryuta; Nakasato, Nobukazu; Igarashi, Kaoru
Abstract: The periodontal ligaments are very important sensory organ for our daily life such as perception of food size or hardness, determination of jaw position, and adjustment of masticatory strength. The sensory properties of the periodontal ligament, especially those of the maxillary and mandibular molars, have not yet been fully investigated. Somatosensory evoked magnetic fields (SEFs) can be measured and evaluated for latency and intensity to determine the sensory transmission characteristics of each body parts. However, previous reports on SEFs in the oral region have only reported differences in upper and lower gingival and lip sensations. In this study, the aim was to clarify these sensory characteristics by measuring SEFs during mechanical stimulation of the periodontal ligament in the maxillary and mandibular first molars. Somatosensory evoked magnetic fields were measured in the contralateral hemispheres of 33 healthy volunteers. Mechanical stimulation of the maxillary and mandibular right first molars, and the left wrist was performed with a specific handmade tool. The first peak latency for the mandibular first molars was 41.7 ± 5.70 ms (mean ± SD), significantly shorter than that for the maxillary first molars at 47.7 ± 7.36 ms. The peak intensity for the mandibular first molars was 13.9 ± 6.06 nAm, significantly larger than that for the maxillary first molars at 7.63 ± 3.55 nAm. The locations in the contralateral hemispheres showed no significant difference between the maxillary first molars and mandibular first molars. These locations were more anteroinferior and exterior than that of the wrist, as suggested by the brain homunculus. Neural signals from the mandibular periodontal ligaments pass faster and more intensely to the central nervous system than those from the maxillary periodontal ligaments, and may preferentially participate in adjustment of the occlusal force and the occlusal position. Abstract : Contralateral hemisphere; Magnetoencephalography; Mechanical stimulation; Periodontal ligament; Primary somatosensory cortex; Somatosensory evoked magnetic field.